Loss Factor of Elastomeric Dampers for Rotating Machinery Application - Asokan, Darvind; Hussain, Jawaid I. Inayat (International Journal of Engineering and Technology, 2018)
Elastomeric dampers have potential application in rotating machinery vibration control. They are however not widely used due to lack of reliable data on their loss factor. Most available data on these dampers are obtained from testing undertaken during stationary condition of the shaft. When the shaft rotates, the dampers are subjected to rotating load that may affect their loss factor. The effect of shaft rotation on the loss factor is experimentally examined in this work. Impact test was used to determine the frequency response function (FRF) of the dampers. For the dampers subjected to rotating load, the loss factor values derived from the FRF was found to be in good agreement with those determined from the half-power bandwidth method. The results further showed that the loss factor at resonant frequency determined from testing of the dampers under stationary shaft condition underestimates the values of the loss factor when the shaft is rotating. The effect of shaft rotation on the values of the damper’s loss factor was more noticeable for the response in the X-direction as opposed to the Y-direction, indicating that pre-strain plays a more dominant role in influencing the loss factor of the dampers compared to the dynamic amplitude.